Assessing Oman's knowledge, attitude and practice regarding tuberculosis: a cross-sectional study that calls for action. (November 2022) - Al Khalili, Sulien; Al Yaquobi, Fatma; Al Abri, Bader; Al Thuhli, Khalsa; Al Marshoudi, Sabria; Al Rawahi, Bader; Al-Abri, Seif
Abstract : First contemporary study to survey national and non-national Omanis on KAP of TB Findings show social media to be the main source of information regarding TB Omanis score high in knowledge and attitude where others have higher practice Abstract: Background: Tuberculosis (TB) remains a major public health issue. Elimination mandates collaboration between decision makers, practitioners and the community. Few studies address the knowledge, attitude and practice (KAP) from countries with low incidence. Aim: Assess KAP regarding TB in Oman. Method: A cross-sectional survey based on validated questionnaire conducted via phone on randomly selected participants. Results: A total of 1048 participants completed the questionnaire. Males accounted for 63% (n=664) of respondents, Omanis 76% (n=796) and 18–39-year-olds 50% (n=527). The overall knowledge was fair (53%), overall attitude scored good and fair (46%) equally and a good score (78%) for overall practice. While female gender associated with higher knowledge (53.9%, n=201), males showed higher attitude and practice, (48.5%, n=322) and (80.3%, n=533) respectively. Omani nationality correlated with higher knowledge (49.1%, n= 391) and attitude (46.9%, n=373) whereas non-Omani nationality correlated with higher practice (85.3%, n=214). Literacy was associated with higher knowledge (73.3%, n=11) and attitude (60%, n=9). Conclusion: Despite efforts by the Ministry of Health, more must be done to raise TB knowledge to encourage preferable attitudes and practice. Interventions to improve KAP are required to speed up disease reduction rate. Utilization of different resources, especially digital platforms, for knowledge dissemination should consider community diversity, including the presence of expatriates.